PENGARUH PENGGUNAAN VLAN PADA SOFTWARE DEFINED NETWORK BERBASIS RYU CONTROLLER - M. Chairul Anam; Hery Dian Septama; Rio Ariestia P; Gigih Forda Nama (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Software Defined Network (SDN) is a network architecture that separates the control plane and data plane in networking devices, which then makes the control plane independent and programmable. The control plane task is taken by the controller, where the controller can manage all the rules in all networking devices, one type of controller is the Ryu controller. VLAN is a network configuration that distributes several different segments to devices connected to the network that can improve network performance. This study aims to determine the performance of VLAN on Software Defined Network using Ryu Controller using a simulation method with 2 scenarios, namely linear topology 3 OpenFlow Switch 30 hosts and linear topology 3 OpenFlow Switch 60 hosts with traffic of 100, 200, 300, and 400 Mb. Testing is carried out using the rest_router app on the Ryu controller which can run static routing without VLAN and with VLAN so that the difference between using VLAN and not can be seen. The test results show that the linear topology of 3 switches, whether 30 hosts or 60 hosts, can work well. Based on the test of QoS parameters Throughput, Packet Loss, and Jitter, the overall of VLAN is less good than without VLAN, with values of 222.9 Mbps, 0%, 0.0000636 s, and 0.0000675 ms, respectively. However, as the number of hosts increases, VLAN is more reliable.